Factors Associated with Family Consent to Organ Donation in Qatar: Results from a Household Survey - Rajvir Singh; Betsy Varughes; Ayman El-Menyar; Saad Shahbal; Yousuf Al Maslamani; Amar Salam; Hassan Al Thani (Masters Program in Public Health, 2022)
Background: Family consent and organ donors rates are colinear to each other. The low consent rate can be influenced by socioeconomic and behavioral factors in the population. This study aimed to assess the influence of sociodemographic and behavioral factors on family consent for organ donation in the household population.Subjects dan Method: This is a secondary data analysis of the cross-sectional research design of 1044 household participants conducted in Qatar on organ donation between October and November 2016. A two-stage systematic random sampling was applied to collect data. The dependent variable was family consent. The independent variables were demographic and behavioral factors such as knowledge, attitude, intention, and beliefs about organ donation. Data were collected using household survey Questionnaire and analyzed using Student t-tests (unpaired), chi-square tests, and multivariate logistic regression analysis. C-statistics were applied to see discriminate accuracy of the developed regression model for family consent.Results: Knowledge (aOR= 1.63; 95%CI= 0.55 to 4.80; p= 0.380), behavioral belief (aOR= 1.11; 95%CI= 0.77 to 1.61; p= 0.580), heard organ donation (aOR= 1.12; 95%CI= 0.71 to 1.76; p= 0.630), registered for organ donation (aOR= 1.11; 95%CI= 0.50 to 2.46; p= 0.800), donated any organ/ blood/tissue (aOR= 1.63; 95%CI= 0.55 to 4.80; p= 0.380) can increased with family consent for organ donation registration. But, it’s not significantly statistic. Attitude (aOR= 1.73; 95%CI= 1.28 to 2.34; p= 0.001), control belief (aOR= 0.74; 95%CI= 0.55 to 0.99; p= 0.050), and Intention (aOR= 7.50; 95%CI= 4.04 to 13.92; p= 0.001) can increased with family consent for organ donation registration and the results were statistically significant.Conclusion: Attitude, control belief, and intention can increase family consent for organ donation registration. Keywords: Family consent, intention, attitude, knowledge, organ donation. Correspondence:Rajvir Singh. Cardiology Research Center, Heart Hospital, Hamad Medical Corporation (HMC), Doha, Qatar, Post Box: 3050; email: rajvir.aiims@gmail.com. Mobile: 97455897044.